Concerning the Landau pole in 3-3-1 models - Dias, A. G.; Martinez, R.; Pleitez, V (Springer, 2005)
Some 3 - 3 - 1 models predict the existence of a non-perturbative regime at the TeV scale. We study in these models and their supersymmetric extensions, the energy at which the non-perturbative limit and a Landau-like pole arise. An order of magnitude for the mass of the extra neutral vector boson, Z', present in these models is also obtained.